(untitled) (Revista Innova Educación, 2020)
This article presents the results of an educational research on pedagogical use in high schools of the heritage of a history museum of Bahía Blanca city (Buenos Aires, Argentina). The aim is to describe the aulic treatment of three history teachers to address local history and its articulation with the national historical processes of the XIXth century. Methodologically it is framed in an ethnographic approach, whose purpose was to look at the school on the everyday scale, to rescue the production of knowledge and practices. The main theoretical debates related to the relationship between museums and schools, the valuation of heritage in Argentine educational laws and the purpose of history as a school discipline in relation to identity processes are briefly addressed interculturality. Two axes of analysis of aulic practices are described: (a) themes of local or national history to be recovered (frontier, national state formation, military campaigns and indigenous peoples) and (b) the pedagogical resources used by teachers to produce historical knowledge (texts, didactic games and drawings). Finally, the possibilities of school use of museums for the teaching of history and the possibilities of appropriation and resignificance of officialized historical accounts are discussed.